Frequency of Self-perceived Stigma in Patients with Polysubstance Abuse Disorder - Ibrahim, Mala; Naeem, Iqra; Ather, Faiza; Rizwan, Maahin (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of self-perceived stigma in patients with polysubstance abuse disorder presenting to a tertiary care psychiatric department. Study design: Cross-sectional observational study. Place and duration of study: This study was conducted in the Department of Psychiatry, Lahore General Hospital, Lahore from November 2024 to April 2025. Methodology: A total of 150 patients aged 18 to 60 years with a clinically confirmed diagnosis of polysubstance abuse disorder and a history of substance abuse for at least 12 months were enrolled through non-probability consecutive sampling. Patients with severe cognitive impairment, acute psychiatric or medical crisis, or inability to understand study procedures were excluded. After informed consent, demographic characteristics, socioeconomic status, educational background, duration of substance abuse, and substance use profile were recorded. Self-perceived stigma was assessed using the Perceived Stigma of Substance Abuse Scale. A score of 19 or above was considered indicative of self-perceived stigma. Data were analyzed using SPSS version 26.0. Stratification was performed, and post-stratification chi-square test was applied. A p-value below 0.05 was considered statistically significant. Results: The mean age of participants was 31.4 ± 9.2 years, and 78.7% were male. The overall mean Perceived Stigma of Substance Abuse Scale score was 21.3 ± 4.6. Self-perceived stigma was identified in 96 patients, giving a frequency of 64.0%. Stigma showed significant association with educational status (p = 0.037), socioeconomic status (p = 0.019), and number of concurrently used substances (p = 0.013). No significant association was observed with gender, marital status, or age group. Conclusion: Self-perceived stigma was highly prevalent among patients with polysubstance abuse disorder. Lower educational attainment, lower socioeconomic status, and greater polysubstance complexity were significantly associated with higher stigma burden. These findings indicate that stigma is an important clinical barrier in this population and should be addressed during routine psychiatric and addiction care.